DOES PLAYING CHESS STRENGTHEN RESILIENCE? - Zoltán MEDVEGY; Máté MIHALOVITS; Mihály MEDVEGY; Imre ZABOS; Tamás STERBENZ (Cluj University Press, 2022)
Previous studies show that physical sports strengthen the psychological immunity, namely the resilience. In our research, we sought to answer the question of whether the above statement was also true for chess, one of the most popular mind sports. The aim of our study is to find correlations between resilience and chess, especially in its competitive form. The American Psychological Association (APA) summarizes the behavior and lifestyle requirements to build resilience in ten points. We used a questionnaire to quantify the level of resilience in persons participating in the research. We divided the participants (396 persons) into three groups based on their chess experience: tournament players, hobby players, and non-players as a control group. We compared the results of the groups in each requirement listed by the APA. Chess players had better results in seven cases of the ten guideline points, while no correlation was found in three cases. Chess competitors are more likely able to accept crises and situations that cannot be changed. They are more focused while pursuing their goals and are able to face and work through challenges more efficiently. They seek the reasons of their failures which helps them to improve their skills. Chess players also tend to maintain a healthier lifestyle. We conclude that chess, especially in its competitive form, can build resilience. Article history: Received 2022 July 27; Revised 2022 September 20; Accepted 2022 September 21; Available online 2022 November 20; Available print 2022 December 20.